Yolk-shell Bi2O3/Bi2O2CO3 heterojunction for enhanced CO2 electroreduction into formate - Xu, Jianzhong (2025)
The integration of nanostructures with compositional optimization is crucial for enhancing their catalytic performance. Herein, a yolk-shell structured catalyst incorporating a Bi2O3/Bi2O2CO3 heterojunction is developed for CO2 electroreduction. This design combines precise nano-structuring with optimized compositional control, expanding the specific surface area, exposing more highly active catalytic sites, accelerating charge transport and improving mass transfer. As a result, the catalyst exhibits superior catalytic performance with 92.3% formate selectivity and a partial current density of −43.3 mA cm−2 at −1.0 V vs. RHE. The precisely engineered nanostructures and heterojunction composition exhibit a good stability during the catalysis with negligible degradation in the catalytic process.